1990
DOI: 10.1177/036354659001800214
|View full text |Cite
|
Sign up to set email alerts
|

Strain measurement in lateral ankle ligaments

Abstract: We measured strain in the lateral ligaments of 10 human cadaver ankles while moving the ankle joint and applying stress in a variety of ways. We studied the anterior talofibular, calcaneofibular, posterior talofibular, anterior tibiofibular, and posterior tibiofibular ligaments. Strain measurements in the ligaments were recorded continuously while the ankle was moved from dorsiflexion into plantar flexion. We then repeated measurements while applying inversion, eversion, internal rotation, and external rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
1
7

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 16 publications
8
119
1
7
Order By: Relevance
“…The present study measured in vivo ATFL lengthening and found strain to be below 10% during both test conditions in the control group. The individuals in both the coper and CAI groups demonstrated greater ATFL strain than the control group for the anterior drawer and inversion test conditions, and these values were also greater than those measured by Colville et al 9 The present study differed in that it did not perform measurements in the fully plantar-flexed position but chose instead to use the anterior-drawer-stress condition and ankle inversion to mimic the clinical anterior drawer test and the ankle position most commonly associated with ATFL injury.…”
Section: Stress Ultrasoundcontrasting
confidence: 44%
See 2 more Smart Citations
“…The present study measured in vivo ATFL lengthening and found strain to be below 10% during both test conditions in the control group. The individuals in both the coper and CAI groups demonstrated greater ATFL strain than the control group for the anterior drawer and inversion test conditions, and these values were also greater than those measured by Colville et al 9 The present study differed in that it did not perform measurements in the fully plantar-flexed position but chose instead to use the anterior-drawer-stress condition and ankle inversion to mimic the clinical anterior drawer test and the ankle position most commonly associated with ATFL injury.…”
Section: Stress Ultrasoundcontrasting
confidence: 44%
“…Ankle inversion, along with plantar flexion, has been shown to result in considerable ATFL strain over other ankle motions, such as dorsiflexion and eversion. 9 Its anatomic orientation indicates that the ATFL functions to restrain plantar flexion, inversion, and talar internal rotation. 34 The use of ultrasound imaging during either an anterior drawer or inversion stress maneuver to quantify the mechanical consequences of lateral ankle injury may be useful to clinicians as a method to better understand CAI and to further develop treatment protocols.…”
Section: Stress Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more than 50 surgical techniques recommended for the treatment of lateral instability of the ankle [2,5,7,13,17,24], and we believe that both the anterior talofibular and the calcaneofibular ligaments (CFLs) must be repaired in order to prevent recurrence and to correct completely the instability [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…고유감각은 인대, 관절낭, 근육, 건, 그리고 피부와 관련된 감각으 로 갑작스러운 변화시 반사적 조절로 발목을 보호하 는 역할을 한다 [5] . 발목의 손상시 급성기에는 통증과 부종, 움직임의 제한이 나타나며 [6] [7] , 시간이 지남에 따라 관절 조직과 고유감각 수용기의 손상으로 이어 져 관절의 움직임과 관절위치감각의 정확성을 손상시 켜 자세조절에 영향을 줄 수 있다 [8] . 이에 발목의 불안 정성은 더욱 악화되어 관절의 재손상을 일으키는 악 순환을 유발한다 [9].…”
unclassified